The Vision of School Administrators Affecting Academic Administration Saraburi Primary Educational Service Area Office 1 - เชาวน์ดี ธนวัฒน์; การีเวท สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this study were to 1) study the level of vision of school administrators, 2) study academic administration in schools, 3) study the relationship between the vision of school administrators and academic administration in schools, and 4) study the impact of the vision of school administrators on academic administration in schools under the Saraburi Primary Educational Service Area Office 1. The research sample consisted of 291 school administrators and teachers in schools under the Saraburi Primary Educational Service Area Office 1, selected using the Krejcie and Morgan sample table and stratified random sampling. The data collection instrument was a 5-level Likert scale checklist with an Index of Content Validity (IOC) between0.50 and 1.00 and a reliability coefficient of .932. The statistical methods used included frequency, percentage, mean (x̄), standard deviation (S.D.), consistency index, reliability coefficient, Pearson correlation, and stepwise multiple regression. The research findings revealed the following: 1) The study of the vision level of school administrators showed that, overall and categorized by aspect, it was at a high level. Ranked from highest to lowest mean score, the aspects were: delegation of authority, The most importantly, being a good role model secondly, disseminating the vision, adhering to the vision, and lastly creating the vision. 2) The overall and individual aspects of academic administration in educational institutions were at a high level. Ranked from highest to lowest mean, these aspects were: teaching and learning management in educational institutions; curriculum development; development of educational media, innovation, and technology; assessment and evaluation of teaching and learning management and registration; and supervision for educational quality development. 3) The study of the relationship between the vision of school administrators and academic administration showed a positive correlation at a relatively high level, statistically significant at the .01level (r = .379). 4) The analysis of the relationship between the vision of school administrators and academic administration, which was statistically significant at the .05 level, included the aspects of being a good role model and delegating authority. The regression analysis in raw and standardized scores was as follows: Ŷ = 3. 050 + 0. 234 x 5 Ẑ = 0. 445 x 4